SYSTEMATIC REVIEW : KONFIGURASI STAF DI DALAM AMBULAN - Sholehah, Baitus (Jurnal Keperawatan Profesional, 2022)
Emergency Medical Service (EMS) is a comprehensive system that provides health and safety services for emergency victims. Ambulances are one component of EMS available 24 hours per day in most hospitals, Ambulance staff provide an important life-saving role in the EMS system. This systematic review discusses the configuration of the staff in the ambulance and is carried out through several stages, namely, formulating research questions, identifying the feasibility of articles, selecting articles to be included, screening articles, and evaluating articles. The article selection process was set out in a systematic review framework and based on that framework, 9 articles were obtained. The articles are then summarized and assessed by JBI in each article. This study looks at the effectiveness of staff configurations in ambulances with various configuration models. The staff configuration model across the country differs in the number of staff the level of training staff has.